Behavioral States Related to Environmental Conditions and Fisheries During Olive Ridley Turtle Migration From Pacific Panama - Guzman, Hector M.; Rogers, Grant; Gomez, Catalina G. (Frontiers in Marine Science, 2019)
Sea turtles migrate from breeding grounds to foraging areas through the territorial waters of several countries. Olive ridleys lack clear migratory routes, which makes it a challenge for conservation. This study aimed to evaluate if the migratory behavior of olive ridleys nesting on the Pacific Coast of Panama is correlated to environmental conditions along the migration and to identify common foraging areas. Thirty-four olive ridley turtles were tagged with satellite transmitters along the Pacific coast of Panama and tracked for up to nine months. A Hidden Markov Model was used to identify behavioral states (foraging and migrating) and their correlation to chlorophyll a concentration, sea surface temperature, eddy kinetic energy, and primary productivity. Turtle tracks overlapped with eddies and industrial fishing areas. The probability of foraging rather than migrating was positively correlated to sea surface temperature, productivity and chlorophyll levels and negatively correlated to eddy kinetic energy. Turtles spent an average 30% of their time migrating and 70% foraging. Only 8.4% of the turtle locations occurred within an eddy, and 82.7% of the locations overlapped with previously described industrial fishing areas. Although this sea turtle species seems to migrate freely, without clear migratory corridors, turtles may have preferred foraging destinations that they travel to through different migratory routes, such as the gulfs of Tehuantepec, Fonseca, and Guayaquil. Turtles traveled up to 6,684 km through nine countries, most of them foraging in oceanic waters in Salvador, Costa Rica, and Panama, which highlights the importance of collaborative conservation strategies throughout foraging and nesting areas. The creation of a regional management unit, including Costa Rica, Panama and Colombia, is discussed based on the observed seasonal overlap with the use of multiple fishing gears in coastal and oceanic fishing areas.